Resistance training restores metabolic alterations induced by monosodium glutamate in a sex‐dependent manner in male and female rats. Issue 8 (27th March 2019) - Quines, Caroline B.; Jardim, Natália S.; Araujo, Paulo Cesar O.; Cechella, José Luiz; Prado, Vinicius C.; Nogueira, Cristina W.
Abstract: Despite resistance exercises being associated with health outcomes, numerous issues are still unresolved and further research is required before the exercise can faithfully be prescribed as medicine. The goal of this study was to investigate whether there are sex differences in resistance training effects on metabolic alterations induced by monosodium glutamate (MSG), a model of obesity, in male and female rats. Male and female Wistar rats received MSG (4 g/kg body weight/day, s.c.) from postnatal day 1 to 10. After 10 days from MSG administration, the rats were separated into two groups: MSG‐sedentary and MSG‐exercised. At postnatal day 60, the animals started a resistance training protocol in an 80 degrees inclined vertical ladder apparatus and performed it for 7 weeks. Control rats received saline solution and were divided in saline‐sedentary and saline‐exercised. Resistance training restored all plasma biochemical parameters (glucose, cholesterol, triglycerides, aspartate aminotransferase, and alanine aminotransferase) increased in male and female rats treated with MSG. The MSG administration induced hyperglycemia associated with a decrease in the skeletal muscle glucose transporter 4 (GLUT4) levels and accompanied by deregulation in proteins, G‐6Pase, and tyrosine aminotransferase, involved in hepatic glucose metabolism of male and female rats. MSG induced dyslipidemia and lipotoxicity in the liver and skeletal muscle of male rats. Regarding female rats, lipotoxicity was found only in the skeletal muscle. The resistance training had beneficial effects against metabolic alterations induced by MSG in male and female rats, through regulation of proteins (GLUT2, protein kinase B, and GLUT4) involved in glucose and lipid pathways in the liver and skeletal muscle. Abstract : 1. Neonatal monosodium glutamate (MSG) administration induced metabolic abnormalities in the blood, liver, and skeletal muscle of adult male and female rat. 2. Resistance training restored metabolic alterations induced by neonatal administration of MSG in a sex‐dependent manner in male and female rats.